Gaya bahasa analogi pada lirik-lirik lagu karya Louane - Salsabila; Ratna; Ekowati, Sri Harini (Franconesia, 2022)
Abstract:This study aims to find out what types of analogy language styles are contained in Louane's song lyrics and how the analogy language style is represented in it. The approach used is descriptive qualitative, with the data collection method is to see notes. Meanwhile, the data analysis technique refers to the three stages of Sugiyono (2008), namely: the data reduction stage, the data presentation stage, and the data withdrawal or verification stage. The data sources used are the lyrics of Louane's song entitled "Chambre 12", "Midi Sur Novembre", "Ecchymoses", and "Immobile" while the data is in the form of fragments of lyrics or sentences contained in the song. The instrument used in this study was the researcher himself with the help of data analysis tables containing four types of analogy language styles, namely comparison, metaphor, personification, and allegory.The results of this study indicate that there are 26 sentences containing analogous language styles, including 11 metaphorical sentences, 9 personification sentences, 3 comparison sentences, and 3 allegorical sentences. The metaphorical sentences contained in the lyrics of Louane's songs are identical to the comparative element, which is not seen explicitly and the comparative element (le comparant) always has a figurative meaning. Then for the personification sentence found, it is characterized by an analogy of an inanimate object or abstract idea (le comparé) given the characteristics possessed by humans or human-like behaviour. As for the sentences containing elements of comparative language style found in the song's lyrics, it has the characteristic that the use of conjunctions such as comme and comparison is always explicit. Then the allegorical sentences found are interpreted using symbols. The comparison in allegory is visualized or depicted in the form of an object so that the comparison is said to be a symbol.